Molecular, serological and in vitro culture-based characterization of Bourbon virus, a newly described human pathogen of the genus Thogotovirus - Lambert, Amy J.; Velez, Jason O.; Brault, Aaron C.; Calvert, Amanda E.; Bell-Sakyi, Lesley; Bosco-Lauth, Angela M.; Staples, J. Erin; Kosoy, Olga I. (Journal of clinical virology, 2015)
•Full-genomic analyses indicate that BRBV is a distinct member of the genus Thogotovirus.•Serological characterization further indicates that BRBV is a distinct member of the genus Thogotovirus.•Growth of BRBV in cell culture suggests association with tick and mammalian hosts.•Preliminary evaluation of BRBV in CD-1 mice in the generation of polyclonal sera reveal that these mice are susceptible to BRBV infection, but not disease. In June of 2014, a previously healthy man from Kansas with a recent history of tick exposure died from complications related to an illness marked by fever, thrombocytopenia and leukopenia. An isolate was derived from the blood of this patient during the course of diagnostic testing. This isolate was subsequently identified as a novel orthomyxovirus of the genus Thogotovirus by next generation sequencing and was named Bourbon virus after the patient’s county of residence. To support research and diagnostic aims, we provide a basic description of Bourbon virus at both the molecular and serological levels. Furthermore, to preliminarily identify potential host and vector range associations we have characterized the growth kinetics of Bourbon virus in a variety of vertebrate and invertebrate cell lines. Bourbon virus was subjected to next generation-high throughput sequencing, phylogenetic, and basic structural protein analyses as well as 2-way plaque reduction neutralization assays. Also, we inoculated a variety of cell types with Bourbon virus and evaluated the growth kinetics by determining viral titers in the supernatants taken from infected cells over time. Bourbon virus possesses 24–82% identity at the amino acid sequence level and low serological cross-reactivity with other Thogotoviruses. In vitro growth kinetics reveal robust replication of Bourbon virus in mammalian and tick cells. Molecular and serological characterizations identify Bourbon virus as a novel member of the genus Thogotovirus. Results from cell culture analyses suggest an association between Bourbon virus and mammalian and tick hosts.